Effects of pueraria lobata combined with high-intensity intermittent training on skeletal muscle quality and gene expression - Zhao, Y.; Guo, M. (Revista Brasileira de Medicina do Esporte, 2021)
Extraction of effective components from Pueraria lobata has important value for skeletal muscle quality and gene expression. The improvement effect of traditional high-intensity intermittent training on skeletal muscle has not been obvious, and it is difficult to guarantee the properties of some volatiles. Based on this, this paper analyzes the effect of high-intensity intermittent training on skeletal muscle quality and gene expression in Pueraria lobata. Based on a brief summary of extraction of Pueraria lobata, status of research on the pharmaceutical components of Pueraria lobata was summarized. Different specimens of Pueraria lobata were selected as research objects, and the process of high-intensity intermittent training was designed. High-intensity intermittent training, solvent extraction and water solvent extraction were combined together to design the fixed-bed continuous extraction scheme. According to the influence of Pueraria lobata on skeletal muscle quality, the influence of intermittent training on skeletal muscle quality was analyzed. The extraction results showed that Pueraria lobata combined with high-intensity intermittent training can effectively improve the content of skeletal muscle and ensure the effective expression of skeletal muscle gene.